ANALISIS MAKNA KONOTATIF LIRIK LAGU JULI PADA ALBUM ES IST JULI - TIRA AMIYATI, AYU (IDENTITAET, 2016)
Humans are social beings and create freely in the language. So that language serves as a controller of every human behavior. Of human behavior raises many variations of languages. Straightforward language, dense, difficult to understand but contains a certain meaning as in the lyrics of the song. The language used in the lyrics of the song is similar to poetry, in the language of emotional and rhythmic, eg allusion, artistic, and soulful. Songwriter uses language style and the election of his own to create a certain feeling and the meaning or sense of values ??within a song. The problems of this research are connotations of what is contained in the fifth song Juli in the album Es ist Juli. The data source of this research was the word and the fifth sentence lyrics (Tränenschwer, Regen und Meer, Sterne, Tage wie Dieser, November) Juli on the album Es ist Juli. Data were analyzed with the theory of the meanings of words are applied by Erdmann of connotations. The method used is a qualitative approach with descriptive method. Results from this study is the fifth song Juli connotations Tränenschwer, Regen und Meer, Sterne, Welt und Schattenreiter implies disappointment. Keywords: connotations, meanings of words, songs the band in Juli